Management of Instrument Sterilization Workflow in Endodontics: A Systematic Review and Meta-Analysis - Mario Dioguardi; Diego Sovereto; Gaetano Illuzzi; Enrica Laneve; Bruna Raddato; Claudia Arena; Vito Carlo Alberto Caponio; Giorgia Apollonia Caloro; Khrystyna Zhurakivska; Giuseppe Troiano; Lorenzo Lo Muzio (International Journal of Dentistry)
Endodontic treatment consists of different working procedures, such as the isolation of the operating field, pulp chamber access, and cleaning and shaping phases with at last the need of a three-dimensional filling of the canals. Each step requires a series of single-use or sterilizable instruments. We have performed a systematic review of different sterilization and disinfection procedures aiming at drawing up a disinfection and sterilization procedure to be used on endodontic instruments. A search on PubMed and Scopus was carried out using the following keywords: “endodontic sterilization,” “endodontic autoclave,” “decontamination dental bur,” “sterilization dental burs,” and “gutta-percha points sterilization.” Eligible articles were included in the qualitative and quantitative analysis. Results of the meta-analysis showed that the most effective method in sterilization is autoclaving. The qualitative analysis showed that the use of single-use or first-use instruments requires presterilization or sterilization procedures, and for reusable tools, attention must be paid to the removal of debris deposited on the blades, not easy to remove manually.